Research of the normal reference values of right ventricular longitudinal strain indices in healthy adults using 2D speckle-tracking echocardiography - Tran, Thanh Dat; Hoang, Anh Tien; Nguyen, Thi Thuy Hang (Tạp chí Y Dược Huế, 2024)
Background: Although right ventricular strain indices obtained from speckle-tracking echocardiography have prognostic value in cardiovascular diseases, normal reference values remain unclear and vary between different manufacturers and software. In Vietnam, there have been no studies addressing this issue. This study aims to determine the reference values of the two strain indices, RVFWLS and RVGLS, and to explore their relationship with age and gender. Method: A total of 132 healthy adults (>18 age) with no medical history of cardiovascular diseases and other internal diseases, who met all inclusion criteria were fully assessed, including clinical assessment, laboratory measurements, and ECG examination. In addition, all participants in our study underwent transthoracic echocardiographic examination, including both conventional parameters and right ventricular strains. Results: The reference values for right ventricular free wall longitudinal strain (RVFWLS) and right ventricular four-chamber longitudinal strain (RV4CLS) are -28.09 ± 3.47 and -24.90 ± 3.05, respectively. The absolute values of RVFWLS and RV4CLS are higher in females than in males, with values of -29.35 ± 3.37 and -26.10 ± 3.04 for females, compared to -26.58 ± 2.97 and -23.47 ± 2.39 for males, respectively, which are statistically significant (p<0.001). Age shows a positive correlation with both RVFWLS and RV4CLS, with correlation coefficients of r = 0.218 and r=0.237, respectively, and statistical significance of p<0.05 and p<0.01. Conclusion: The index RVFWLS and RV4CLS using speckle-tracking echocardiography are significantly higher in females than in males (p<0.001). Therefore, caution should be exercised when using these values in clinical practice